Gambaran Kejadian Ikutan Pasca Imunisasi Vaksinasi Covid-19 pada Remaja - Amanda Gabriella; Yufitriana Amir; Sri Utami (Jurnal Vokasi Keperawatan (JVK), 2022)
Vaccination is one of the efforts to prevent and overcome the Covid-19 pandemic. Currently, vaccination can be given to adolescents aged 12-17 years. Vaccines used in national programs are declared safe and effective, but there is no one type of vaccine that is guaranteed to be free of effects or Post Immunization Adverse Events (AEFI). This study was to determine the description of the incidence of post-covid-19 immunization in adolescents. This research is quantitative research with a descriptive research design. This research was conducted at SMPN 37 Pekanbaru City with 100 samples taken using a random sampling method. The analysis used is univariate analysis. The result most of the respondents were 14 years old which found 62 respondents (62%). women with a total of 68 respondents (68%) and men with 32 respondents (32%), class VIII with a total of 17 respondents (17%), and class IX with a total of 83 respondents (83%), all respondents had received the Covid-19 vaccination. 19 doses 1 and 2 with 95 respondents (95%) Sinovac, 4 respondents (4%) Pfizer and 1 respondent (1%) Moderna. The results of the study showed a picture of post-covid-19 vaccination in adolescents, as many as 83 respondents (83%) experienced experiences Adverse Events after Post-Covid-19 Vaccination Immunizations and 13 respondents (13%) did not experience experiences Adverse Events after Post-Covid-19 Vaccination Immunizations. Based on the results of this study, the researcher can conclude that the average student of SMP N 37 Pekanbaru City experiences Adverse Events after Post-Covid-19 Vaccination Immunizations.